Metastatic conversion of cells by expression of human papillomavirus type 16 E6 and E7 genes. - Chen, L (1993)
The human papillomavirus type 16 (HPV-16) is a DNA tumor virus highly associated with cervical carcinoma. Viral DNA from HPV-16 is found in primary tumors and their metastatic lesions. To investigate the role of HPV-16 oncoproteins in the development of cancer metastasis, the E6 and E7 genes from HPV-16 were inserted into retrovirus and introduced into nonmetastatic mouse cell lines. Expression of either of the viral genes from HPV-16 made the cells metastatic in nude mice. In contrast, expression of the E6 and E7 genes of HPV type 6 (HPV-6b), which is frequently found in nonmalignant HPV-associated diseases, did not. The metastatic ability of cells transduced with viral genes of HPV-16 did not correlate with their growth rate or sensitivity to destruction by natural killer cells. Our results demonstrate that expression of oncogenic proteins of HPV-16 can cause tumor metastasis and implicate HPV-16 in an important role regarding the progression of HPV-associated human cancers.